Zombie international currency: The Pound Sterling 1945-1973 - Maylis Avaro (Graduate Institute of International and Development Studies, 2020)
This paper provides new evidence on the decline of sterling as an international currency, focusing on its role as foreign exchange reserve asset under the Bretton Woods era. Using a unique new dataset on the composition of foreign exchange reserves of central banks, I show that the shift away from the sterling occurred earlier than conventionally supposed for the countries not belonging to the sterling area. The use of sterling has been described as freely chosen, imposed by the Bank of England or negotiated. I argue that the sterling area was a captive market as the Bank of England used capital controls, commercial threats and economic sanctions against sterling area countries to limit the divestments of their sterling assets. This management of the decline of sterling benefited mostly Britain and the City of London but represented a cost for sterling area countries and the international monetary system.
Keywords: N24; F31; E58; 330; Monetary and financial history; Foreign exchange; International monetary system